Light-Controlled Nanosystem with Size-Flexibility Improves Targeted Retention for Tumor Suppression - Luo Huanhua; Kong Li; Zhang Feng; Huang Chenglong; Chen Jiayi; Zhang Hongbo; Yu Han; Zheng Song; Xu Hongwei; Zhang Yiran; Deng Lianfu; Chen Gang; et al. (WILEY-V C H VERLAG GMBH, 2022)
Although great promise has been achieved with nanomedicines in cancer therapy, limitations are still encountered, such as short retention time in the tumor. Herein, a nanosystem that can modulate the particle size in situ by near-infrared (NIR) light is self-assembled by cross-linking the surface-modified poly(lactic-co-glycolic acid) from the up-conversion nanoparticle with indocyanine green and doxorubicin-nitrobenezene-polyethylene glycol (DOX-NB-PEG). The nanosystem with its small size (approximate to 100 nm) achieves better tumor targeting, while the PEG on the surface of the nanosystem can effectively shield the adsorption of proteins during blood circulation, maintaining a stable nanostructure and achieving good tumor targeting. Moreover, the nanosystem at the tumor realizes the rapid shedding of PEG on its surface by NIR irradiation, and the enhanced cellular uptake. At the same time, aggregation occurs inside the nanosystem to form bigger particles (approximate to 600 nm) in situ, prolonging the retention time at the tumor and producing enhanced targeted therapeutic effects. In vitro data show higher cellular uptake and a higher rate of apoptosis after irradiation, and the in vivo data prove that the nanosystem have a longer residence time at the tumor site after NIR irradiation. This nanosystem demonstrates an effective therapeutic strategy in targeted synergistic tumors.